Marketing Strategy Development of Processed Seafood Souvenir During the Covid-19 Pandemic at IKM “Bahek Ewaki”, Central Bangka Regency - Eni Karsiningsih; Anisa Anisa; Rufti Puji Astuti (Faculty of Fisheries and Marine Science, Brawijaya University, 2023)
Marketing strategy development is one of the important elements that must be possessed by every Small and Medium Industry (IKM). The Covid-19 pandemic has caused the income of IKM